(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Persisters are phenotypic variants of normal susceptible bacterial populations that survive prolonged exposure to high doses of antibiotics and are responsible for relapse of infection. Acinetobacter baumannii formed highest percentage of persister cells against rifampicin followed by amikacin and least against colistin. In the present study, three different anti-persister approaches were employed to target the persister cells. First, curcumin synergistically increased reactive oxygen species (ROS) production in combination with colistin, reducing significantly the survival of persister cells. Second, exogenous supplementation of metabolites viz. glucose, fructose or citrate or osmolytes increased proton- motive force (PMF) that facilitated amikacin uptake leading to decreased newlinepersister cells survival. Third, quorum-quenching enzyme lactonase effectively reduced persister cells against antibiotics in biofilm formed in its presence. These strategies can be effectively employed as treatment options with anti-persister potential for the control of chronic and relapsing A. baumannii infections.